Infanzia e linguaggi narrativi in Dino Buzzati - Lepri, Chiara (Studi sulla Formazione/Open Journal of Education, 2014)
The paper aims to illustrate the world of childhood in buzzatian fiction from the literature (specially La famosa invasione degli orsi in Sicilia, 1945) and from the conception of fantasy literature, until the collaboration with the "Corriere dei Piccoli" magazine (1968-1969). In terms of narrative languages, special attention deserves the narrative through words and images. In this sense, Buzzati still represents a significant ’standard of comparison’ in the context of studies of children’s literature.